Short‐term intravenous insulin infusion is associated with reduced expression of NADPH oxidase p47phox subunit in monocytes from type 2 diabetes patients. (10th July 2012) - Vaquer, Guillaume; Magous, Richard; Cros, Gérard; Wojtusciszyn, Anne; Renard, Eric; Chevassus, Hughes; Petit, Pierre; Lajoix, Anne‐Dominique; Oiry, Catherine
Abstract: Hyperglycemia is a well‐known inducing factor of oxidative stress through activation of NADPH oxidase. In addition to its plasma glucose lowering effect, insulin may also have antioxidant activity and was shown to downregulate NADPH oxidase expression in vitro . In this study, we show that a short‐term (3‐day) intravenous insulin infusion in patients with type 2 diabetes induces normalization of both glycemia and mRNA expression of circulating monocyte p47 phox subunit.